2019
DOI: 10.1111/ijfs.14278
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nutraceutical potential of the microalgae Chlorella vulgaris and Arthrospira platensis

Abstract: The microalgae Chlorella vulgaris and Arthrospira platensis were evaluated as nutraceuticals. It was observed that Arthrospira platensis is richer in saturated fatty acids (FA) and Chlorella vulgaris richer in monounsaturated FA. Within polyunsaturated FA (PUFA), n3 PUFA content was below 1% in Arthrospira sp and over 10% in Chlorella vulgaris. This microalga had the lowest polyphenolic content. The highest value was found in the aqueous extract of Arthrospira platensis, 334 AE 32 mg GAE per 100 g dw. Regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Our results also showed that the presence of non-polar compounds such as chlorophylls, carotenoids and lipids, in addition to some phenolic compounds, gives a high reducing antioxidant power (FRAP) activity, showing significant differences between the aqueous (1 st step) and ethanolic extracts (2 nd step) (see Figure 5A and B). It has been concluded by several authors who worked with different species of microalgae that phycobiliproteins, phenolic compounds, carotenoids and chlorophylls contribute significantly to the antioxidant capacity of these aquatic organisms (Goiris et al, 2012;Matos et al, 2020;Pan-utai & Iamtham, 2019). On the other hand, the obtained extract from the 3 rd extraction step did not show any antioxidant activity based on the DPPH and FRAP methods (data not shown).…”
Section: Antioxidant Activity Of Extractsmentioning
confidence: 85%
See 2 more Smart Citations
“…Our results also showed that the presence of non-polar compounds such as chlorophylls, carotenoids and lipids, in addition to some phenolic compounds, gives a high reducing antioxidant power (FRAP) activity, showing significant differences between the aqueous (1 st step) and ethanolic extracts (2 nd step) (see Figure 5A and B). It has been concluded by several authors who worked with different species of microalgae that phycobiliproteins, phenolic compounds, carotenoids and chlorophylls contribute significantly to the antioxidant capacity of these aquatic organisms (Goiris et al, 2012;Matos et al, 2020;Pan-utai & Iamtham, 2019). On the other hand, the obtained extract from the 3 rd extraction step did not show any antioxidant activity based on the DPPH and FRAP methods (data not shown).…”
Section: Antioxidant Activity Of Extractsmentioning
confidence: 85%
“…In a recent study carried out by Matos et al (Matos et al, 2020), Spirulina ethanolic extracts also showed greater antioxidant activity assessed by the FRAP method compared to aqueous extracts, but no activity was observed by the DPPH method. In another study, the authors obtained results that clearly showed that both the highest J o u r n a l P r e -p r o o f antiradical and antioxidant activity, determined by the DPPH method, were highly correlated with aqueous extract of S. platensis (Shalaby & Shanab, 2013).…”
Section: Antioxidant Activity Of Extractsmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, PC is commonly extracted from the dried biomass of the Cyanobacteria Arthrospira platensis [43,121]. Therefore, it is a widely available, known and researched organism, not only regarding growth conditions [122], but also in a medical and cosmetic scope [123][124][125], as a nutrient removal and effluent treatment agent [126,127], and as a nutritional and health supplement [128,129]. In the European Union, extracts from this microalgae are used as a food colorant in confectionary products [110].…”
Section: Phycocyaninmentioning
confidence: 99%
“…Microalgae are essential live diet in fish hatcheries that meet the complete nutritional requirements; therefore, microalgae cells, as well as their valuable contents, are considered nutritious for the aquatic animals (Sharawy et al, 2020; Yadav et al, 2020). Arthrospira platensis (formally named Spirulina ) is a filamentous cyanobacterium (fresh blue‐green algae) and rich in several Phyto‐contents, including essential amino and fatty acids, riboflavin, iron, carotenoids and pigments (Matos et al, 2020; Zaki et al, 2021). The inclusion of A .…”
Section: Introductionmentioning
confidence: 99%